(untitled) (Equilibrium: Jurnal Pendidikan, 2019)
The spatial physical construction that takes place in the Wae bath becomes the driving force of the shift in spatial patterns and space utilization that impact on social change in the local community. The purpose of this study is to understand the process of social change that occurred and the impact of the local community caused by visitors bathing Wae Pellae. This research is a qualitative research using observation technique, interview and documentation. Data analysis was done descriptively through data reduction, presentation and data processing, and conclusion. The results showed that the spatial physical changes in Wae Pellae bathing in its development caused the high intensity of visitors coming from outside, impact on the happening of social change, pattern of interaction of society with visitor happened in the form of exchange of interest. Wae Pellae Baths as a place to conduct socio-economic production, while the negative impact is the birth of various forms of changes in mindset and behavior patterns. Keywords: Physical Spatial, Social Change, Wae Pellae